FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIR MENJADI SEORANG AKUNTAN PUBLIK - Divina Fitriana; Harti Budi Yanti (STMIK Widuri Jakarta, 2023)
The purpose of this research is to test and find out the influence of accounting students' interest in Financial Awards, Work Environment, social values, and Labor Market Considerationson accounting students' interest in becoming professional public accountants in active Bachelor of Accounting studentsclass of 2019at Trisakti University. This research is a type of quantitative research. The sampling technique of this research is purposivesamplingmetode, with the number of samples used as many as 100 samples. This research uses multiple linear regression method using SPSS version 25 as a data analysis technique. The result of the research shows that factors Financial Awards, Work Environment, and Labor Market Considerations have positive and significant affect on Accounting StudentsInterestin choosing a carrer to became a public accountant. While the social values has negative or no significant affect on Accounting Students Interest in choosing a carrer to became a public accountant